Development of SNAP tag and horseradish peroxidase-based nanobodies as secondary antibody mimics for indirect immunoassays - Sheng, Wenjie; Justus Liebig University Giessen (My University, 2025)
Immunoassays are widely used in diagnosis and biomedical research for the detecting and quantifying specific biomolecules. Based on antigen-antibody interaction system, immunoassays enable the localization, qualitative analysis and quantification of target proteins. Among these, indirect immunoassays offer enhanced signal amplification and flexibility by using fluorescence-conjugated secondary antibodies. However, conventional secondary antibodies, predominantly immunoglobulin (IgG), present challenges due to their large size (150 kDa). Moreover, most animal-derived antibodies raise ethical concerns and exhibit batch-to batch variability. In contrast, small antibody fragments such as nanobodies (Nbs), which are derived from camelids and consist of only a single variable domain, are significantly smaller size (15 kDa) and can be efficiently produced using mammalian cell expression system. In this study, five previously established anti-mouse and anti-rabbit IgG secondary Nbs were selected and incorporated with a self-labeling SNAP-tag. The SNAP-tag (20 kDa) catalyzes the covalent, site-specific attachment of O6-benzylguanine (BG)-modified fluorophores to recombinant Nbs anti-IgG-SNAP proteins. These Nbs anti-IgG-SNAP were expressed in HEK293T cells. Following a rapid and straightforward conjugation protocol involving the SNAP-tag and BG modified Alexa Fluor dyes, the specific detection capability of Nbs anti-IgG-SNAP for mouse- or rabbit-derived primary antibodies was validated using flow cytometry and multi-color fluorescence microscopy. Additionally, these secondary nanobodies were further developed to be combined with horseradish peroxidase (HRP) and the recombinant Nbs anti-IgG-HRP proteins were expressed in HEK293T cells. Their functionality was validated as secondary antibodies in Western blot (WB) and tyramide signal amplification (TSA)-based multiplex immunofluorescence (mIF) assays. The results demonstrated that Nbs anti-IgG-SNAP and Nbs anti-IgG-HRP specifically bound to mouse or rabbit antibodies, exhibiting fluorescence intensities, quantitative validity and specificity comparable to conventional anti-mouse or anti-rabbit secondary antibodies. Moreover, their cost-effectiveness, scalable expression, easy of purification and simple site-specific conjugation procedures present an innovation alternative to traditional animal-derived antibody production, ensuring greater standardization and reproducibility in research applications. Taking together, these findings suggest that recombinant anti-mouse and anti-rabbit IgG secondary nanobodies present a promising and reliable alternative to traditional secondary antibodies in various indirect immunoassays.
Keywords: ddc:610